2000
DOI: 10.1016/s0014-5793(00)01286-2
|View full text |Cite
|
Sign up to set email alerts
|

Induction of cell death by the lysosomotropic detergent MSDH

Abstract: Controlled lysosomal rupture was initiated in lysosome-rich, macrophage-like cells by the synthetic lysosomotropic detergent, O-methyl-serine dodecylamide hydrochloride (MSDH). When MSDH was applied at low concentrations, resulting in partial lysosomal rupture, activation of pro-caspase-3-like proteases and apoptosis followed after some hours. Early during apoptosis, but clearly secondary to lysosomal destabilization, the mitochondrial transmembrane potential declined. At high concentrations, MSDH caused exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
210
2
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 225 publications
(216 citation statements)
references
References 26 publications
3
210
2
1
Order By: Relevance
“…3). Dependent on the magnitude of lysosomal rupture, cell proliferation is stimulated or arrested by a minor or a somewhat more pronounced lysosomal destabilization, respectively, while apoptosis or necrosis have been found to follow moderate or major destabilization, respectively (Li et al, 2000, Terman et al, 2010. Consequently, the amelioration of LMP by chelating lysosomal redox-active iron in a non-redox-active form ought to reduce radiation sensitivity.…”
Section: Lysosomal Iron and Ionizing Irradiationmentioning
confidence: 99%
“…3). Dependent on the magnitude of lysosomal rupture, cell proliferation is stimulated or arrested by a minor or a somewhat more pronounced lysosomal destabilization, respectively, while apoptosis or necrosis have been found to follow moderate or major destabilization, respectively (Li et al, 2000, Terman et al, 2010. Consequently, the amelioration of LMP by chelating lysosomal redox-active iron in a non-redox-active form ought to reduce radiation sensitivity.…”
Section: Lysosomal Iron and Ionizing Irradiationmentioning
confidence: 99%
“…4 Severe oxidative stress has also been associated with LMP and consequent necrosis. 10 Extracellular application of 0.01-1 mM peroxide is physiologically relevant and broadly mimics the release of endogenous H 2 O 2 . 11 For example, activated neutrophils generate up to 6 Â 10 À14 mol H 2 O 2 /h per cell, generating a local concentration of 10-100 mM H 2 O 2 .…”
mentioning
confidence: 99%
“…The higher levels in plasma and lower activities in lysosomal fractions of these enzymes, as observed in the present study, may be due either to the infiltration of inflammatory cells or due to isoprenaline-mediated lysosomal fragility by Ca 2+ overload. A necrotic cell death can be triggered by a too strong lysosomal membrane permeabilization (Li et al 2000) and oxygen free radicals are primarily responsible for the release of lysosomal hydrolases. It has also been suggested that abnormal release and activation of lysosomal enzymes during ischemia and other potentially lethal events may contribute to the tissue damage.…”
Section: Resultsmentioning
confidence: 99%